Perlindungan Hukum terhadap Kreditur Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Tambuann, Bertua Putra (Wajah Hukum, 2024)
After the Constitutional Court decision Number 18/PUU-XVII/2019, the execution of fiduciary collateral created a sense of injustice and lack of legal certainty for creditors as money lenders. This decision eliminates the Creditor's authority to execute fiduciary collateral objects, as previously stated in article 15 paragraph 3 of the fiduciary law. As a result, the Creditor experienced problems in executing the fiduciary guarantee object after the Debtor failed to fulfil its obligations. The purpose of this writing is to find out what the ideal form of legal protection for Creditors is after the Constitutional Court decision Number: 18/PUU-XVII/2019. The research method used in this research is normative juridical, which only focuses on legal materials using a conceptual approach and a statutory approach. The results of this research are Constitutional Court Decision Number: 18/PUU-XVII/2019 which has made the fiduciary law lose its role as the law establishing fiduciary guarantee institutions. Fiduciary guarantee certificate has lost its identity because the executorial power over the object of fiduciary guarantee which is considered to be the same as the district court decision no longer applies if the Debtor does not voluntarily hand over the object which is the object of fiduciary guarantee to the Creditor.